Potential Causes Of Poverty In The City Of Probolinggo - Amani, Tatik; Rahajeng, Yekti; Hermanto, Hermanto (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2021)
Poverty is a situation where humans cannot achieve their basic requirements. This has become a standard problem experienced by every country. The research object aims to find the potential causes of poverty in the Probolinggo by examining the effect of the potential for education, unemployment, and inflation simultaneously, partially and dominantly, on poverty. The study used a quantitative method of causal relationships, 391 RTM respondents with cluster sampling technique sampling. The data analysis method used a validity test, reliability test, classical assumption test, multiple linear regression analysis, and determination coefficient analysis. The conclusion from the hypothesis testing in this research is the variables of education, unemployment, and inflation have a significant and partial effect on poverty in Probolinggo City, while the most dominant potential effect on poverty is education. The result of the determination coefficient analysis is 71.9%. The causes of poverty in the city of Probolinggo are education, unemployment, and inflation. From the research results, the local government should continue to motivate and make people aware of the importance of education, improve skills as a means of overcoming unemployment, increase economic growth so the inflation can be suppressed, and the problem of poverty is resolved.